The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3168/jds.2020-18653
|View full text |Cite
|
Sign up to set email alerts
|

Predicting dairy cattle heat stress using machine learning techniques

Abstract: The objectives of the study were to use a heat stress scoring system to evaluate the severity of heat stress on dairy cows using different heat abatement techniques. The scoring system ranged from 1 to 4, where 1 = no heat stress; 2 = mild heat stress; 3 = severe heat stress; and 4 = moribund. The accuracy of the scoring system was then predicted using 3 machine learning techniques: logistic regression, Gaussian naïve Bayes, and random forest. To predict the accuracy of the scoring system, these techniques use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…The THI is normally used to summate the intensity of heat stress on dairy cows [ 14 ]. The high THI values (>84) showed that the cows were under moderate heat stress during the month of August and September.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The THI is normally used to summate the intensity of heat stress on dairy cows [ 14 ]. The high THI values (>84) showed that the cows were under moderate heat stress during the month of August and September.…”
Section: Discussionmentioning
confidence: 99%
“…The increased standing time for the CNT group suggested that the cows were benefitting from the cooling effects of the sprinklers. Whereas the 2CS increased in standing time suggested increase in exposing more body surface area for heat abatement to reduce heat load [ 14 , 22 ]. The decreased standing time in the 4CS consequently increased lying time could be associated with reduced heat load.…”
Section: Discussionmentioning
confidence: 99%
“…Management of dairy farms through machine learning-based analysis of milking features has received increased attention in recent years [4,6,8,[22][23][24][25][26][27][28]. The next step is globalisation of a machine-learning based expert system from milking parameters.…”
Section: Discussionmentioning
confidence: 99%
“…PS has been developed and refined as a numerical scale to grade the obvious respiratory dynamics and behaviors [59,88,123,124]. A recent study utilized a score consisting of RR and various panting characteristics to assess heat strain in grazing dairy cows [133]. This score is very similar to PS, using a 0 to 4 scale, where 0 represents that the cow is under no heat strain and 4 represents that the cow is moribund.…”
Section: Panting Scorementioning
confidence: 99%